Socio-emotional outcomes in deaf education: Evaluation of current approaches - Goh, Yee Ching (2016)
There have always existed the debate of whether the acquisition of sign language facilitates or hinders the education of deaf children. To date, three major approaches are still being employed in this field – oral approach, total communication, and bilingualism. Findings have been conflicting on the outcomes of deaf students admitted to each of these approaches. Despite the socio-emotional development of this group of children being viewed as important, there has been relatively less research done in comparing how the modes of communication employed in educational instructions affect the deaf child in their psychological wellbeing. This paper aims to evaluate the effectiveness of the each approach in terms of cognitive competence and personal and social development. Through a comprehensive review of current literature, the bilingualism method appears to emerge as the most beneficial approach to cultivating better psychosocial well-being in a deaf child. More research has to be done to validate the assumptions made and make adaptations to the way the method is employed around the world to continue to benefit more deaf children.